Thyme Sediments for Energy Storage Systems and Its Benefit Evaluations for Agricultural Economics - ŞAHİN DEMİREL, Ayça Nur and DEMİREL, Serkan (ISPEC Tarım Bilimleri Dergisi, 2024)
In this study, the use of thyme residue as an electrode in energy storage systems was analyzed. The electrochemical analysis started by analyzing the CV in the ±0.5V range. However, due to low current values and misleading data, the measurement range was extended to ±1V and ±2V. Current plateaus of varying widths were observed in the ±0.5V and ±1V ranges at all scan rates. However, as the scan rates increased, redox peaks started to appear at the thyme sediment electrodes. At a scan rate of 200 mV/s, two different redox events were detected at 0.35 V and 1.4 V. Charge-discharge and power performance analyses were performed on capacitors made with thyme sediment electrodes. The results show that thyme sediment, an organic material, can store energy in capacitors and supercapacitors can be formed with a capacitance of about 101 F g-1. As a result of the determination that thyme residue can be used as an alternative electrode material, evaluation analyzes were also made in terms of agricultural economy and it was concluded that this discovery could lead to significant economic developments for both the energy sector and agriculture.